Trends in the seasonal cycle of modelled streamflow across Australia, 1980–2018. Issue 3 (10th February 2023) - Coleman, Rachel Lauren; Jain, Shaleen
Abstract: Australian seasonal streamflow cycles represent diverse weather and climate variations and distinctive influences from coupled ocean-atmospheric phenomena, including monsoons, frontal systems, and El Nino-Southern Oscillation. Streamflow strongly modulates the health of ecosystems and is inextricably linked to communities through consumptive use and cultural and spiritual practices. To better understand the potential impacts of a changing climate, a comprehensive trend analysis of streamflow variability resolved at daily scales is pursued for 35 rivers across Australia using a serially complete modelled streamflow dataset (1979–2018) from the GloFAS-ERA5 operational global river discharge reanalysis. Analysis consisted of quantile regression to identify direction and significances of trends in low, median, and high flows, K-means clustering to identify grouping of data with similar features, and Poisson regressions to identify rainfall changes during low and high rainfall seasons. Results present comprehensive decreases at low, median, and high flows in southern continental river streamflow. Northern continental streamflows display increases and decreases throughout the year across flows, with increases more prevalent. Trends within upper and lower portions of the flow distributions reveal unique sub-seasonal time windows in the extremes, thus underscoring that trends across the full distribution of streamflow are necessary to understand vulnerability to human and environmental systems. HIGHLIGHTS: Modelled streamflow, historical rainfall seasonal, and trend analyses. Clustering for identification of different annual streamflow cycles across Australia. Low and high streamflows and rainfall volume window trends. Increasing rainfall trends during the high rainfall window and mixed increases and decreases in streamflow across the northern cluster. Decreasing streamflow trends dominant across southern Australia.